Global patterns and mechanisms of decoupling municipal solid waste generation from economic growth - Zhang, Chenyi; Dong, Huijuan; Zeng, Yong; Geng, Yong; Liu, Xiao; Chen, Wen; Fujii, Minoru (Environmental impact assessment review, 2025)
To explore the driving forces and seek solutions to the municipal solid waste (MSW) challenge, this study aims to uncover the decoupling patterns and mechanisms of global MSW generation by applying Tapio decoupling analysis and the environmental Kuznets curve (EKC) model. Thirty countries with different development levels were selected as research samples. The results show that the decoupling of MSW from economic development has deteriorated since 2010, with middle-income countries exhibiting worse performance than high-income countries. Several countries, including Australia, Belgium, Spain, the United Kingdom, Hungary, Japan, Bulgaria, Costa Rica, and Ukraine, have achieved continuous decoupling. Furthermore, an inverted U-shaped EKC model was validated between per capita MSW generation and per capita national income, with the EKC turning point at 32,626 USD per capita national income. This indicates that high-income countries have a relatively easier pathway to achieve the decoupling of per capita MSW generation. Finally, we proposed several practical solutions for achieving global MSW decoupling and MSW peaks. •This study investigates how to achieve global MSW decoupling and peak.•The EKC turning point was estimated to be 37,466 USD national income per capita.•Economic development is found to be the primary driver for MSW generation.•Mechanism to decouple economic development and MSW generation is proposed.